Effect of Umbilical Cord-derived Mesenchymal Stem Cell Secretome on Corpus Cavernosum Elastography Results in Patients with Severe Erectile Dysfunction Non-responsive to Sildenafil - Pratama, Andi Ahmad Thoriq; Rahardjo, Paulus; Atmaja, M Hidayat Surya; Supardi, Petrus; Margiana, Ria (Universitas Islam Bandung, 2025)
Erectile dysfunction is one of the most common male sexual dysfunctions, defined as the inability to get or maintain an erection, and its prevalence is increasing over time. The current treatment, using a phosphodiesterase-5 inhibitor like sildenafil, only offers a temporary solution. Secretome, a bioactive substance derived from mesenchymal stem cells from the umbilical cord, has shown remarkable regenerative capabilities. This study aims to explore the potential of administering umbilical cord-derived mesenchymal stem cell secretome to patients with severe erectile dysfunction and evaluate its impact on the stiffness of the corpus cavernosum using elastography in the flaccid phase. This study employed a pre-experimental design with a pre-post test. It involved seven patients who came to Dr. Soetomo Hospital with severe erectile dysfunction that was unresponsive to sildenafil. Elastography evaluation, including strain and shear wave elastography, was performed before and one month after secretome injection, which was carried out from March to April 2024. Data were analyzed using the paired sample t-test when the data distribution was normal and the Wilcoxon test when the data distribution was not normal. There were statistically significant changes (p<0.05) in all patients who underwent strain and shear wave elastography of the corpus cavernosum before and one month after secretome administration, indicating an improvement in stiffness. In conclusion, intracavernosal administration of umbilical cord-derived mesenchymal stem cell secretome has demonstrated promising results in treating severe erectile dysfunction non-responsive to sildenafil therapy. These results include improved penile tissue in the corpus cavernosum, as evidenced by decreased stiffness on elastography.